Tipologi Literatur Keagamaan Aktivis Muslim Kampus di Kota Jambi - Ali Muzakir (Jurnal Lektur Keagamaan, 2013)
This paper attempts to discuss and analyze the Muslim activist’s literatures in three universities in Jambi city. This study argues that the trend of Muslim literatures could be seen in the proliferation of Islamic media in the public sphere. The study finds out that the dynamic of the Muslim activist literatures in Jambi have been mushroomed and popular. This study uses two methods: interview and framing analysis. The former is used in collecting the literatures, while the later is used in examining the content and discourse. Using framing analysis, the author will discuss and analyze some religious characteristics i. e. literal shari’a oriented, criticism against the Jew and Christian, and criticism against America. Thereby, some literature promote Islamic teachings radically and to keep fit in operating dakwah agenda through out the life. Keywords: Campus Moslem Activists, Religious Literature, Salafy